2021
DOI: 10.3390/neurolint13040060
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Aetiology and Collateral Status in Acute Ischemic Stroke Patients Receiving Reperfusion Therapy—A Meta-Analysis

Abstract: Background: The interplay between collateral status and stroke aetiology may be crucial in the evaluation and management of acute ischemic stroke (AIS). Our understanding of this relationship and its level of association remains sub-optimal. This study sought to examine the association of pre-intervention collateral status with stroke aetiology, specifically large artery atherosclerosis (LAA) and cardio-embolism (CE), in AIS patients receiving reperfusion therapy, by performing a meta-analysis. Methods: Releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…A higher pc-ASPECT in our analysis was associated with a good clinical outcome at 3 months too. This is reasonable since we know that pc-ASPECT detects the areas of brain tissue that are already ischemic before the treatment [19], probably reflecting the status of the collateral circulation [20]. Anyhow, the evaluation of the score is difficult with CT, due to posterior fossa beam hardening artefacts, particularly in the brainstem; these limits may cause low sensitivity and great interobserver variability [21].…”
Section: Discussionmentioning
confidence: 99%
“…A higher pc-ASPECT in our analysis was associated with a good clinical outcome at 3 months too. This is reasonable since we know that pc-ASPECT detects the areas of brain tissue that are already ischemic before the treatment [19], probably reflecting the status of the collateral circulation [20]. Anyhow, the evaluation of the score is difficult with CT, due to posterior fossa beam hardening artefacts, particularly in the brainstem; these limits may cause low sensitivity and great interobserver variability [21].…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin and eosin (H&E) staining was the most commonly performed histological analysis, used by 19 studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 25 , 26 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Martius Scarlet Blue (MSB) [ 16 , 22 , 23 , 24 , 40 ] and Elastica van Gieson (EVG) [ 18 , 28 , 30 , 32 , 33 , 35 ] staining were both selected in 5 studies, Prussian Blue in 3 [ 18 , 28 , 33 , 35 ], Masson’s trichrome in 2 [ 36 , 37 ], and Ladewig’s trichrome [ 39 ], Von Kossa [ 39 ], naphthol AS-D [ 39 ], chloroacetate [ 39 ], and Mallory’s phosphotungstic acid-hematoxylin [ 18 ] were included once each. One study used scanning electron microscope [ 32 ], and eight studies employed immunohistochemistry in their analyses [ 13 , 15 , 16 , 18 , 22 ,…”
Section: Resultsmentioning
confidence: 99%
“…One study [ 26 ] reported greater WBC content in strokes of non-cardioembolic origin, and another study [ 21 ] reported greater WBC content in cardioembolic strokes. Seven studies found no significant association [ 13 , 14 , 17 , 19 , 20 , 22 , 28 , 30 ]. Eight studies with 339 participants were included in the meta-analysis studying WBC content and aetiology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, studies aimed at delineating the stroke etiology, acute therapeutic options, biomarkers of prognosis, and poststroke long-term management of IE patients will provide insights to improve clinical outcomes in these high-risk patients. 11 - 13 …”
Section: Introductionmentioning
confidence: 99%